The California Border Health Collaborative: A Strategy for Leading the Border to Better Health - Matthews, Charles Edwards; Wooten, Wilma; Gomez, María Gudelia Rangel; Kozo, Justine; Fernandez, April; Ojeda, Victoria D. (Frontiers in Public Health, 2015)
There are hundreds of people and organizations working on border health issues in the California–Baja California border region trying to protect and improve health. These efforts are being conducted without a collaborative structure that integrates jurisdictions and organizations. Thus, there is a need to coordinate these organizations to work together and benefit from their collective effort and each other’s best practices. The outcome of such an effort could effectively improve the health in the border region. The newly developed “California Border Health Collaborative” unites organizations and provides the leadership and collaborative culture to positively improve the health of the border region; it is referred to as the “Collaborative.” This article describes the developmental process of this Collaborative, including partner engagement, governance, strategic planning, key elements for success, the roles of multi-level jurisdictions, and policy implications. This paper focuses on describing the preparation and processes that created the U.S./California side of this binational collaborative effort and is a strong reflection of the theory of border collaboration as described by Denman and De Sonora (1) in “Working beyond Borders: A Handbook for Transborder Projects in Health.”